Bioenergy from stillage anaerobic digestion to enhance the energy balance ratio of ethanol production - Fuess, Lucas Tadeu; Garcia, Marcelo Loureiro [UNESP] (Elsevier B. V., 2015)
The challenges associated with the availability of fossil fuels in the past decades intensified the search for alternative energy sources, based on an ever-increasing demand for energy. In this context, the application of anaerobic digestion (AD) as a core treatment technology in industrial plants should be highlighted, since this process combines the pollution control of wastewaters and the generation of bioenergy, based on the conversion of the organic fraction to biogas, a methane-rich gaseous mixture that may supply the energetic demands in industrial plants. In this context, this work aimed at assessing the energetic potential of AD applied to the treatment of stillage, the main wastewater from ethanol production, in an attempt to highlight the improvements in the energy balance ratio of ethanol by inserting the heating value of methane as a bioenergy source. At least 5-15% of the global energy consumption in the ethanol industry could be supplied by the energetic potential of stillage, regardless the feedstock (i.e. sugarcane, corn or cassava). The association between bagasse combustion and stillage anaerobic digestion in sugarcane-based distilleries could provide a bioenergy surplus of at least 130% of the total fossil fuel input into the ethanol plant, considering only the energy from methane. In terms of financial aspects, the economic gains could reach US$ 0.1901 and US$ 0.0512 per liter of produced ethanol, respectively for molasses- (Brazil) and corn-based (EUA) production chains. For large-scale (∼1000 m(3)EtOH per day) Brazilian molasses-based plants, an annual economic gain of up to US$ 70 million could be observed. Considering the association between anaerobic and aerobic digestion, for the scenarios analyzed, at least 25% of the energetic potential of stillage would be required to supply the energy consumption with aeration, however, more suitable effluents for agricultural application could be produced. The main conclusion from this work indicates that anaerobic processes should be considered the core technology to treat stillage, based mainly on the attractive relation energy generation-financial return and on the possibility to keep the advantages inherent to the common fertigation when using the treated effluent in agriculture.
Keywords: Anaerobic digestion; Bioenergy generation; Economic benefits; Energy recovery; Stillage